Studying Audit Quality as a Link between Accounting Conservation and Aggregated Accounting-based Earnings Quality: Theoretical and Empirical Perspectives from Emerging Economy - Dr. Yousaf Khan; Muhammad Waseem Arshad; Iqra Bashir; Dr Muhammad Nadeem; Muhammad Usman Ramzan Gujjar (Kurdish Studies, 2022)
Research Purpose—the Paper has explored the nexus between accounting conservatism and accounting-based earnings quality. This paper also examines how Audit Quality moderates this nexus in the emerging economy (Pakistan) context. Design/methodology/approach—the top 70 non-financial firms from 2014 to 2023 are included in the study sample and are sourced from the sites of PSX and NBP. The study used various estimators including Pooled OLS, Random Effects, and Fixed Effects models to ascertain which model well predicts the results of the Research Study. The Fixed Effects Model estimates better coefficients than the others in light of carrying out different tests for testing the reported hypothesis. Research Findings—the empirical findings depict that Accounting Conservatism has a significant positive impact on accounting-based Earnings Quality. Likewise, Audit quality has been found to positively moderate the link between the said variables, which boosts earnings quality by reducing earnings management in the respective firms. Research limitations—The sample size of this Research study is somewhat limited (small), and thus the effects of the findings cannot be applied to all unlisted firms; rather, they can only be used to firms that are listed on the Pakistan Stock Exchange. Originality—this study is the new one to explore the effect of Audit Quality (Big4) on the link between Accounting conservatism (C-Score) and earnings. It can explain part of the reasons for the mixed and inconsistent results in the literature. Practical implications—Policymakers should concentrate their attention on accounting standards and policies, mainly on firms that operate in highly competitive sectors to reap the most results. This study has an immense influence on encouraging non-adopter countries to implement Accounting Conservatism for the transparency of Earnings quality by discouraging Agency conflict and Earnings Management in all relevant Firms.